2007
DOI: 10.1111/j.1749-7345.2005.tb00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Larval Development of the Giant River Prawn Macrobrachium rosenbergii at Different Ammonia Concentrations and pH Values

Abstract: The effect of ammonia and pH levels on giant river prawn Macrobrachiurn rosenbergii larvae were evaluated to provide science-based information on safe levels of ammonia and pH for larviculture. Survival rate, developmental stage, and larval weight gain were determined for larvae kept in water with total ammonia (NH,-N) concentrations of 0, 1,2,4, and 8 mgK and pH 7,8, and 9. The trials were conducted in two phases: phase 1, larvae from stages I through VIII and phase 2, larvae from stage VIII until metamorphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
1
15
0
2
Order By: Relevance
“…In this way, NH 3 accumulates in juveniles, thus altering their growth and causing death. Similar explanations were put forward by Mallasen and Valenti (2005) for larval development and survival of the giant river prawn M. rosenbergii at different NH 3 concentrations. Straus et al .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In this way, NH 3 accumulates in juveniles, thus altering their growth and causing death. Similar explanations were put forward by Mallasen and Valenti (2005) for larval development and survival of the giant river prawn M. rosenbergii at different NH 3 concentrations. Straus et al .…”
Section: Discussionsupporting
confidence: 66%
“…Mallasen and Valenti (2005) reported significantly lower survival rates (0–20%) of M. rosenbergii larvae at total ammonia concentrations from 1 to 8 mg L −1 (0.43–3.41 mg L −1 of non‐ionized ammonia) in pH 9, although the weight gain (1.572–2.931 mg range) of larvae did not differ among the different ammonia concentrations. Straus, Robinette and Heinen (1991) studied the toxic effect of non‐ionized ammonia (NH 3 ) on post‐larval and early juvenile of M. rosenbergii and reported that early juveniles (around 0.5 g size) were more tolerant of high NH 3 than postlarvae.…”
Section: Introductionmentioning
confidence: 92%
“…). The levels of ammonia and nitrite remained below the lethal concentration, 0.5 and 0.1 mg L −1 , respectively (Mallasen & Valenti , ). This suggests that recirculating systems provided with large crushed mollusc shell biofilters (~25% the volume of the rearing hatchery tank) may support an intensification of at least 140 larvae L −1 without affecting water quality.…”
Section: Discussionmentioning
confidence: 99%
“…During the progression of the experiment the NO 3 -N concentrations increased progressively up to 7.6 mg/L, however, it remained well below the toxic levels for M. rosenbergii larval culture [34]. Management of ammonia in the larval rearing systems of M. rosenbergii is important as significantly lower survival rates (0-20%) of larvae were noticed at total ammonia concentrations ranging from 1 to 8 mg/L with 0.43-3.41 mg/L non-ionic ammonia at pH 9 [35]. The higher relative percent survival (22.86%) obtained in the reactor integrated experimental system proved the impact of the technology in enhancing the larval survival.…”
Section: Discussionmentioning
confidence: 95%